Efficient CO2 electroreduction over pyridinic-N active sites highly exposed on wrinkled porous carbon nanosheets - Li, Hongqiang; Xiao, Nan; Hao, Mingyuan; Song, Xuedan; Wang, Yuwei; Ji, Yongqiang; Liu, Chang; Li, Chen; Guo, Zhen; Zhang, Feng; Qiu, Jieshan (Chemical engineering journal (Lausanne, Switzerland : 1996), 2018)
[Display omitted] •Pitch derived N-doped carbons were fabricated by template method and NH3 etching.•Active pyridinic-N highly exposed on the surface of conductive carbon frameworks.•This novel carbon sheets exhibit superior activity in electrocatalytic CO2 reduction.•The synergistic porosity, N-doping and 2D morphology lead to a high performance. The development of an efficient catalyst system for the electrocatalytic reduction of CO2 into highly valuable chemicals is a significant research subject. However, conventional metal electrocatalysts usually suffer from high cost, poor durability and limited accessible active sites. The exploration of high-performance and cost-effective metal-free catalysts with abundant exposed active sites is of urgent and highly desirable for CO2 reduction reaction (CO2RR). Herein, we report a facile yet efficient post-etching strategy to fabricate wrinkled N-doped porous carbon nanosheets (WNCNs) as a promising electrocatalyst for selectively producing CO with high stability. The catalyst exhibits negligible onset overpotential (−0.19 V) for CO production and a maximum Faradaic efficiency (FE) of 84% at an overpotential of −0.49 V. The superior performance is credited to the robust and nanoporous two-dimensional (2D) architecture, which are in favor of fast charge transfer, CO2 adsorption as well as the highly exposure of pyridinic-N active sites. First-principles density functional theory (DFT) calculations confirm that the pyridinic-N can offer favorable binding sites to COOH∗ intermediates and facilitate their subsequent catalytic reduction. This work highlights a new class of low-cost and scalable electrocatalysts for synthetic CO production from CO2 under benign conditions for application.